Secured iota enabled micropayment transaction crypto-platform with discretionary mining capabilities and miner nomination based on first-price sealed bid auction theory - Amin, H.M Sadman; Raﬁ, Nakhla; Suﬁyan, Zahin; Anjum, Syeda Afrida (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2019.